In vitro propagation of bulblets and LC–MS/MS analysis of isosteroidal alkaloids in tissue culture derived materials of Chinese medicinal herb Fritillaria cirrhosa D. Don - Chang, Hung-Chi (Bot Stud, 2020)
BACKGROUND: Fritillaria cirrhosa, an important Chinese medicinal herb, is a Class-III protected and highly exploited species by pharmaceutical industry. Dwindling wild populations of species are unable to meet market demand. Therefore, this study was carried out to develop an in vitro propagation method for bulblet production. Also, the study aimed to carry out LC–MS/MS analysis of tissue culture-derived bulblets and callus for the presence of isosteroidal alkaloids (peimissine, verticine, and verticinone), and compare its quantities with commercially available crude drug samples. RESULTS: In vitro seed germination (91%) of F. cirrhosa was achieved on Murashige and Skoog’s basal medium (MSBM) supplemented with 6-benzylaminopurine (1 mg L(−1)) and α-naphthalene-acetic-acid (0.4 mg L(−1)). On transfer of germinated seeds from Petri-dishes to glass bottles containing hormone-free MSBM, 37.5% of seedlings developed bulblets after 3 months of incubation. Regeneration and multiplication of bulblets were achieved by culture of transverse sections of bulblets on 1/2 X MSBM. By repeated subcultures at an interval of 2 months, 3072 bulblets weighing 1270 g could be produced at the end of 5th subculture. LC–MS/MS analysis showed a significant presence of peimissine in in vitro bulblets while callus incubated in the dark showed presence of peimissine and verticine. CONCLUSION: The study reports an efficient in vitro propagation method of bulblets production of F. cirrhosa and presence of some isosteroidal alkaloids in tissue culture-derived bulblets and callus. The study could be of immense help in production of F. cirrhosa bulblets and callus under laboratory conditions round the year. Also, these results can be used further to investigate production of isosteroidal alkaloids in bioreactors at commercial scale using liquid and cell suspension cultures. Thus, we not only can reduce our dependence on collections from natural habitats, but also can help in in situ conservation of this important species.